2007
DOI: 10.1007/s10725-007-9165-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis of CIPK gene family in Arabidopsis and Populus

Abstract: Calcium serves as a second messenger in various signal transduction pathways in plants. CBL-interacting protein kinases (CIP-Ks), which have a variety of functions, are involved in calcium signal transduction. Previous, the studies on CIPK family members focused on Arabidopsis and rice. Here, we present a comparative genomic analysis of the CIPK gene family in Arabidopsis and poplar, a model tree species. Twenty-seven potential CIPKs were identified from poplar using genome-wide analysis. Like the CIPK gene fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
62
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 41 publications
11
62
0
Order By: Relevance
“…However, the transcript levels of PeCBL1 and PeCBL9 decreased at 24 h, and in converse, the levels of PeCBL3, PeCBL4, PeCBL6, and PeCBL10 increased under MgCl 2 treatment. The PeActin gene was served as expression control Plant Growth Regul (2008) 56:129-140 137 active than in Arabidopsis during the evolution of genomes, which is coincident with that in the PtCIPK family (Yu et al 2007). Moreover, our analysis indicated that there are 3 paralogous pairs in PtCBL family and more existing than in Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the transcript levels of PeCBL1 and PeCBL9 decreased at 24 h, and in converse, the levels of PeCBL3, PeCBL4, PeCBL6, and PeCBL10 increased under MgCl 2 treatment. The PeActin gene was served as expression control Plant Growth Regul (2008) 56:129-140 137 active than in Arabidopsis during the evolution of genomes, which is coincident with that in the PtCIPK family (Yu et al 2007). Moreover, our analysis indicated that there are 3 paralogous pairs in PtCBL family and more existing than in Arabidopsis.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies have demonstrated the functional conservation of the CBL-CIPK pathway in Populus (Yu et al, 2007), grape (Weinl and Kudla, 2009), sorghum (Li et al, 2010), and maize (Chen et al, 2011). Enhanced tolerance to diverse stresses has also been regularly observed in transgenic Arabidopsis because of the overexpression of CIPKs (Zhao et al, 2009;Chen et al, 2012), rice (Xiang et al, 2007), tomato Huertas et al, 2012), tobacco (Tripathi et al, 2009), and apple (Hu et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…CBL proteins have no enzymatic activity and function by interacting with and regulating a group of serine-threonine protein kinases called CBL-interacting protein kinases (CIPK) (Luan et al 2002). To date, genes encoding CBLs and CIPKs have been found in all sequenced higher plant species (Yu et al 2007;Zhang et al 2008). Genome-wide analysis has revealed ten CBL members in Arabidopsis, rice, and poplar .…”
Section: Introductionmentioning
confidence: 99%